Reactive nodular fibrous pseudotumor: A rare mesenchymal tumor (Indian Journal of Case Reports, 2019)
Reactive nodular fibrous pseudotumor (RNFP) is a recently described non-neoplastic mesenchymal lesion arising from the gastrointestinal tract, mesentery, or retroperitoneum. It is a rare entity with only a few cases reported in literature so far and is less aggressive when compared to other mesenchymal lesions such as gastrointestinal stromal tumor (GIST) or fibromatosis. Here, we present the case of a 20-year-old female who presented with a huge abdominal mass. Contrast-enhanced computed tomography was suggestive of pseudopapillary tumor of the pancreas. The patient underwent exploratory laparotomy and excision of the mass in toto along with sleeve gastrectomy and splenectomy. Post-operative histopathology confirmed the entity to be RNFP. This case illustrates the need for keeping RNFP in mind as a differential diagnosis in a case of large abdominal mass as it has a fairly good prognosis with no reported recurrence after surgical excision.